2009
DOI: 10.1007/s11701-009-0136-8
|View full text |Cite
|
Sign up to set email alerts
|

Tumor enucleoresection in robot-assisted partial nephrectomy

Abstract: The objective of this study is to describe our technique and results of the enucleoresection technique in robot-assisted partial nephrectomy. The patient is positioned in full flank position. Three robotic arms of a da Vinci system and an assistant's port are used. The renal hilus is freed, the kidney mobilized and the site of the partial excision prepared. The vessels are clamped with a bulldog. The capsula of the kidney is incised circular about 5 mm around the tumor. A pseudocapsula of compressed healthy ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The PK forceps were used to manipulate the tumour away from normal parenchyma to aid dissection. While enucleation and enucleoresection techniques are described and associated with excellent outcomes , it is the preference of the authors to excise the tumour with a clear margin of normal parenchyma. This stage required deft ‘duck and weave’ movements of the surgical assistant with suction, to maintain visualization of the resection plane (Fig.…”
Section: Methods and Surgical Techniquementioning
confidence: 99%
“…The PK forceps were used to manipulate the tumour away from normal parenchyma to aid dissection. While enucleation and enucleoresection techniques are described and associated with excellent outcomes , it is the preference of the authors to excise the tumour with a clear margin of normal parenchyma. This stage required deft ‘duck and weave’ movements of the surgical assistant with suction, to maintain visualization of the resection plane (Fig.…”
Section: Methods and Surgical Techniquementioning
confidence: 99%
“…The overlying perinephric fat and a small margin of normal renal parenchyma are resected en bloc with the tumour. Mottrie et al [31] were the first to describe a robotic tumour enucleoresection technique, identifying a plane 0.5 cm away of the tumour and dissecting almost exclusively bluntly. Later, Boris et al [32] also reported a RPN enucleating technique for hereditary multiple tumours.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, 20 studies met the inclusion criteria and were included in the analysis. Of these, five were single-arm studies [12] , [13] , [14] , [15] , [16] and 15 were comparative studies [5] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] . Review of the quality assessment and level of evidence revealed a moderate to high risk of bias overall, and a moderate to very low level of evidence ( Supplementary Fig.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Five studies analyzed the impact of the resection technique used on outcomes of interest. Mottrie et al [12] reported on a series of 17 patients who underwent robot-assisted enucleoresection. The authors underlined that owing to compression of the tumor on the normal renal parenchyma, a pseudocapsule of healthy parenchyma a few millimeters away from the tumor usually offered a safe plane for blunt dissection.…”
Section: Evidence Synthesismentioning
confidence: 99%